ISOLASI, IDENTIFIKASI DAN UJI AKTIVITAS ANTIOKSIDAN SENYAWA FLAVONOID DAUNBINAHONG (Anredera cordifolia (Ten.) Steenis) - Rahmawati, Lina (Chem Info Journal, 2013)
Binahong (Anredera cordifolia (Ten.) Steenis) can heal burns, wounds like after the surgery, rheumatoid arthritis, gout, heart swelling, typhoid, and stroke. Binahong leaves contain flavonoid compound that has an antioxidant activity. The aims of this research are isolation, identification, and antioxidant activity test of flavonoid compound from Binahong leaves. This research was started by extraction, partition, purification, and followed by the purity test. Identification of flavonoid structure was conducted using shift reagent on UV-Vis spectrophotometer. Antioxidant activity test used DPPH method, which brings in the value of IC50. Characterization by shift reagents on UV-Vis spectrophotometer resulted that the compound was 3, 5, 3’,4’- tetrahydroxiflavonol. The results of antioxidant activity test indicate that ethyl acetate extract and C fraction from Binahong leaves have a potentiality as antioxidant.